FEATURES OF TEACHING TRAINING PROCESS IN MEN’S COLLEGE ZAPADNO UKRAINSKAYA (XIX EARLY XX V.) - Pakholok, R. I. (Continuing Professional Education: Theory and Practice, 2019)
The article analyzes the characteristics of teaching learning process in male Western schools in the nineteenth early twentieth century. The author reveals the basic forms, means, methods, principles of teaching boys, traces their development. Outlines the structure of educational institutions that vytrymuvalasya in contemporary gymnasium, high school curricula analyzed, the features guide the educational process in schools. Outlines how assessment methods to encourage pupils. Analysis of lessons and excursions as main teaching ways of working with pupils. Singled out the principles upon which was built the learning process in schools. Characteristic of educational tools that teachers in their different exchange gymnasium. Among the training of male educational institutions were singled out textbooks, and manuals, teaching materials, classrooms and libraries. It is shown that in the period in the evolution of male high school didactic process: from passive forms of learning teachers move to active, apply new pedagogical ideas. Singled out recommendations for further scientific studies: an analysis of textbooks, teaching certain subjects in the gymnasium.